2017
DOI: 10.3389/fphar.2017.00302
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 Receptor Plays a Negative Modulation on N-type Calcium Channel

Abstract: The sigma-1 receptor is a 223 amino acids molecular chaperone with a single transmembrane domain. It is resident to eukaryotic mitochondrial-associated endoplasmic reticulum and plasma membranes. By chaperone-mediated interactions with ion channels, G-protein coupled receptors and cell-signaling molecules, the sigma-1 receptor performs broad physiological and pharmacological functions. Despite sigma-1 receptors have been confirmed to regulate various types of ion channels, the relationship between the sigma-1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…To test the impact of σ1 activation on endothelial barrier function, we performed a concentration‐response study with the highly selective σ1 agonist, PRE‐084, at concentrations of 1, 5, 10, 50, 100, 150, and 200 μM, based on previously reported data 6,40‐42 . The results show a concentration‐dependent increase in barrier enhancement (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 92%
“…To test the impact of σ1 activation on endothelial barrier function, we performed a concentration‐response study with the highly selective σ1 agonist, PRE‐084, at concentrations of 1, 5, 10, 50, 100, 150, and 200 μM, based on previously reported data 6,40‐42 . The results show a concentration‐dependent increase in barrier enhancement (Figure 1A,B).…”
Section: Resultsmentioning
confidence: 92%
“…FRET and coimmunoprecipitation experiments demonstrated that N-type channels and Sig-1R form protein-complexes when these proteins are expressed in HEK293 cells. The authors of this study proposed that Sig-1R agonists produce a conformational change in these protein complexes that negatively regulates N-type channels (Zhang et al, 2017).…”
Section: Regulation Of Cav Channels Through Sig-1r’s Activationmentioning
confidence: 99%
“…The Sigma-1 receptor could enhance or inhibit Ca 2+ channel activity through either direct or indirect actions (Kourrich et al., 2012). To date, only few studies have shown the direct action of Sigma-1 receptor on Ca 2+ channels in the CNS (Mueller et al., 2013; Zhang et al., 2017). In cultured retinal ganglion cells, the activation of Sigma-1 receptor by SKF10047 inhibited Ca 2+ currents, and this effect was abolished by Sigma-1 receptor antagonist BD 1047.…”
Section: The Physiological Roles Of Sigma Receptor In the Central Nermentioning
confidence: 99%
“…In addition, the association between the Sigma-1 receptor and Ca 2+ channel was shown by Co-IP experiments (Mueller et al., 2013). N-type Ca 2+ currents from cholinergic interneurons in rat striatum were also reduced by Sigma-1 receptor agonists (SKF-10047 and Pre-084) (Zhang et al., 2017), this inhibition was prevented by Sigma-1 receptor antagonist BD 1063. Sigma-1 receptors and N-type Ca 2+ channels bind together, which is demonstrated by FRET assays and Co-IP (Zhang et al., 2017).…”
Section: The Physiological Roles Of Sigma Receptor In the Central Nermentioning
confidence: 99%